Dynamics 365 essentials : getting started with Dynamics 365 apps in the common data service - Critchley, Sarah (Apress, 2020)
Discover what the Common Data Service is and how Dynamics 365 fits in the Power Platform. Learn how to set up core Dynamics 365 Customer Engagement functionality and build more customized processes using model-driven apps. This book covers the Dynamics 365 Online system for sales, customer service, marketing, field service, and Outlook integration. In this second edition, core platform changes from the Common Data Service are included and you will know what this means for Dynamics 365. Updated features include processes, the latest form and view designer, and Business Process Flows. The book also includes new chapters on portals and power virtual agents. After reading Dynamics 365 Essentials, you will have mastered the core functionality available in Dynamics 365 CE and model-driven applications, and will be able to set it up for a range of different business scenarios. You will: Set up the core standard features of Dynamics 365 CE Create model-driven apps within Dynamics 365 customized to specific business needs Customize Dynamics 365 CE and leverage process automation functionality through the UI Learn about the Common Data Service for Apps.